A Study on Aluminium Levels in Patients Undergoing Haemodialysis at a Tertiary Care Hospital - Kader, Hafeez Abdul; Meera, Neelathahalli Kasturirangan; Siddique, Abubakar; Ahmed, Ashfaque (Indian Journal of Pharmacy Practice)
Introduction: Aluminium studied as a potentially toxic metal and is commonly found in earth’s crust. Aluminium toxicity may lead to: aluminium-induced bone disease, microcytic anaemia and neurological manifestation, such conditions more particular seen in patients with chronic renal failure and principally patients on haemodialysis. Objectives: The objective of our study was to measure a serum aluminium levels in patients undergoing haemodialysis at tertiary care hospital, Bengaluru. Materials and Methods: This was a prospective study, conducted on 50 patients who were on maintenance haemodialysis for more than 6 months. 5 ml of the blood was drawn from the antecubital vein from the patient before haemodialysis process. Collected blood samples were estimated for aluminium levels by GFAAS. The dialysis fluid and RO water were also tested similarly for presence of aluminium to correlate the possible contamination. Results: The results were; 6(12%) patients had serum aluminium levels within baseline i.e. <20μg/L, 18(36%) patients had serum aluminium levels between 21-60μg/L and 26 (52%) of the patients had serum aluminium levels above 60μg/L. The aluminium content varied in the dialysate fluid reaching greater than the standard safety limit. Conclusion: In our study we found that aluminium toxicity is a serious problem in patients undergoing haemodialysis. Patients performing haemodialysis for longer period showed higher level of aluminium. Patients age of 50 years and on haemodialysis for duration 3 years need to be monitored carefully for aluminium toxicity. The major source of elevated serum aluminium in our study participants appears to be dialysate fluid, use of aluminium utensils, OTC products and food habits of consult patients.
Keywords: Aluminium toxicity; Haemodialysis; CRF; Nephrology; GFAAS.